Glass Child dalam Kerangka Teori Locus of Control - Moza A. Fadilah; Nauroh N.A.T. Elsifa; Ragil W. Hernawati; Ulfa Masfufah (Flourishing Journal, 2023)
Glass child, is a child who lives and grows up with siblings with disabilities or chronic illnesses. Glass child behavior is influenced by external and internal factors. External factors come from stimulus from outside that encourages the glass child to respond, while internal factors include the perceptions and emotional turmoil that the glass child is feeling. The aim of this research is to examine the glass child phenomenon through the locus of control theory by Rotter, by analyzing the dynamics of behavior in glass children. The method used in this research is a literature study. Through the analysis of eight journals, it can be seen that the locus of control in glass children tends to lead to an external locus of control. Namely, the glass child believes that as an individual has no control over her or his behavior, but is controlled by things outside himself such as other people, fate, in this case, such as parents, and other family members, who have high expectations, as well as environmental perceptions. Belief in fate, namely having a sibling with a disability. In addition, individuals with an extremely external locus of control tend to be more easily stressed and experience depression. AbstrakGlass child, anak yang tinggal dan tumbuh bersama dengan saudara dengan disabilitas maupun penyakit kronis. Perilaku glass child dipengaruhi oleh faktor eksternal dan faktor internal. Faktor eksternal yaitu ketika ada stimulus dari luar yang mendorong glass child untuk memberikan respon, sedangkan faktor internal mencakup persepsi dan gejolak emosi yang dirasakan glass child selama tumbuh dengan saudara disabilitas dan memiliki penyakit kronis. Tujuan dari penelitian ini adalah menelaah fenomena glass child melalui teori locus of control oleh Julian B. Rotter, dengan menganalisis dinamika perilaku pada glass child. Metode yang digunakan dalam penelitian ini adalah studi literatur. Melalui analisis delapan jurnal dan artikel dapat diketahui bahwa locus of control pada glass child cenderung mengarah ke locus of control eksternal. Yaitu, bahwa glass chlid percaya bahwa sebagai individu ia tidak memiliki kendali atas perilakunya, melainkan dikendalikan oleh hal hal diluar dirinya seperti orang lain, dan nasib. Orang lain, dalam hal ini seperti orang tua, dan anggota keluarga yang lain, yang berekspektasi yang tinggi, serta persepsi lingkungan terhadap saudara. Kepercayaan terhadap nasib yaitu nasib memiliki saudara kandung dengan disabilitas sebagai alasan yang akan menentukan diri dan perilakunya dimasa depan. Selain itu, individu dengan locus of control eksternal yang ekstrim cenderung lebih mudah stress.